Effects of BMI on the risk and frequency of AIS 3+ injuries in motor‐vehicle crashes12. (12th March 2013) - Rupp, Jonathan D.; Flannagan, Carol A.C.; Leslie, Andrew J.; Hoff, Carrie N.; Reed, Matthew P.; Cunningham, Rebecca M.
Abstract Objective: Determine the effects of BMI on the risk of serious‐to‐fatal injury (Abbreviated Injury Scale ≥ 3 or AIS 3+) to different body regions for adults in frontal, nearside, farside, and rollover crashes. Design and Methods: Multivariate logistic regression analysis was applied to a probability sample of adult occupants involved in crashes generated by combining the National Automotive Sampling System (NASS‐CDS) with a pseudoweighted version of the Crash Injury Research and Engineering Network database. Logistic regression models were applied to weighted data to estimate the change in the number of occupants with AIS 3+ injuries if no occupants were obese. Results: Increasing BMI increased risk of lower‐extremity injury in frontal crashes, decreased risk of lower‐extremity injury in nearside impacts, increased risk of upper‐extremity injury in frontal and nearside crashes, and increased risk of spine injury in frontal crashes. Several of these findings were affected by interactions with gender and vehicle type. If no occupants in frontal crashes were obese, 7% fewer occupants would sustain AIS 3+ upper‐extremity injuries, 8% fewer occupants would sustain AIS 3+ lower‐extremity injuries, and 28% fewer occupants would sustain AIS 3+ spine injuries. Conclusions: Results of this study have implications on the design and evaluation of vehicle safety systems.